3D printing topographic cues for cell contact guidance: A review. (June 2022) - Lai, Huinan; Gong, Bo; Yin, Jun; Qian, Jin
Graphical abstract: Highlights: Outline of 3D printing technologies for manufacturing topographic cues. Summary of cellular responses to topographic cues in cell culture experiments. Overview of both physical and biological mechanisms of contact guidance. Abstract: Contact guidance for cell outgrowth refers to the phenomenon of the topography of the extracellular matrix regulating cell behaviors and functions. In tissue engineering, scaffolds with appropriate topographic cues for cell contact guidance show great potential in facilitating tissue repair and regeneration. Advanced 3D printing technology enables the fabrication of intricate and accurate structures for the study of the cellular responses and underlying mechanisms of contact guidance. This review focuses on 3D printing topographic cues for cell contact guidance. First, typical 3D printing technologies for manufacturing topographic cues are covered. Subsequently, cellular responses on 3D printing topographic cues in cell culture experiments are summarized. Then, the mechanisms of contact guidance on cell outgrowth are recapitulated. Finally, the major challenges and future perspectives for this field are discussed.